KONSTRUKSI HUKUM EFEKTIFITAS PERAN ORGANISASI PROFESI KESEHATAN BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2023 TENTANG KESEHATAN - Sutrisno (Universitas Karya Husada Semarang, 2023)
This study aims to analyze (1) the role of professional health professional organizations in providing legal protection to current health workers before the issuance of Law Number 23 of 2023 concerning Health and (2) the legal construction of the effectiveness of the role of health professional organizations based on Law Number 23 of 2023. The research method used is normative legal research methods with statutory and conceptual approaches. The results of the study show that (1) the role of professional health worker organizations in providing legal protection to current health workers prior to the issuance of Law Number 23 of 2023 concerning Health will provide legal protection for their members as in the case of the Indonesian National Nurses Association (PPNI) organization which will act as a mediator in medical disputes faced by its members and will help members who are deemed guilty if according to PPNI the nurse has carried out procedures in accordance with her professional duties; and (2) the legal construction of the effectiveness of the role of health professional organizations based on Law Number 23 of 2023 is not effective. The legal construction for the regulation of professional health worker organizations indicates the existence of the phenomenon of fragmentation and amputation of the role of health worker organizations so that their role becomes ineffective.